Safety and immunogenicity of a virus-like particle pandemic influenza A (H1N1) 2009 vaccine: results from a double-blinded, randomized Phase I clinical trial in healthy Asian volunteers. - Low, J; Lee, L; Ooi, E; Ethirajulu, K; Yeo, P; Matter, A; Connolly, J; Skibinski, D; Saudan, P; Bachmann, M; Hanson, B; Lu, Q; et al. (2014)
METHODS: A novel, fully bacterially produced recombinant virus-like particle (VLP) based influenza vaccine (gH1-Qbeta) against A/California/07/2009(H1N1) was tested in a double-blind, randomized phase I clinical trial at two clinical sites in Singapore. The trial evaluated the immunogenicity and safety of gH1-Qbeta in the presence or absence of alhydrogel adjuvant. Healthy adult volunteers with no or low pre-existing immunity against A/California/07/2009 (H1N1) were randomized to receive two intramuscular injections 21 days apart, with 100μg vaccine, containing 42μg hemagglutinin antigen. Antibody responses were measured before and 21 days after each immunization by hemagglutination inhibition (HAI) assays. The primary endpoint was seroconversion on Day 42, defined as percentage of subjects which reach a HAI titer ≥40 or achieve an at least 4-fold rise in HAI titer (with pre-existing immunity). The co-secondary endpoints were safety and seroconversion on Day 21. RESULTS: A total of 84 Asian volunteers were enrolled in this study and randomized to receive the adjuvanted (n=43) or the non-adjuvanted (n=41) vaccine. Of those, 43 and 37 respectively (95%) completed the study. There were no deaths or serious adverse events reported during this trial. A total of 535 adverse events occurred during treatment with 49.5% local solicited symptoms, of mostly (76.4%) mild severity. The most common treatment-related systemic symptom was fatigue. The non-adjuvanted vaccine met all primary and secondary endpoints and showed seroconversion in 62.2% and 70.3% of participants respectively on Day 21 and Day 42. While the adjuvanted vaccine showed an increased seroconversion from 25.5% (Day 21) to 51.2% (Day 42), it did not meet the immunogenicity endpoint. CONCLUSION: In summary, non-adjuvanted gH1-Qbeta showed similar antibody mediated immunogenicity and a comparable safety profile in healthy humans to commercially available vaccines. These results warrant the consideration of this VLP vaccine platform for the vaccination against influenza infection (HSA CTC1300092).